HUBUNGAN POSISI KERJA, POSISI KEPALA DAN JARAK JANGKAUAN DENGAN KELELAHAN FISIK PEKERJA BATIK DI DESA KAUMAN SOKARAJA - Harwanti, Siti; Aji, Budi; Ulfah, Nur (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2016)
Handmade batik worker is a job used sit position. Indecent sit position will cause workers feel fatigue faster. The objective of this research is to know correlation work sit position with physical fatigue at handmade batik workers. This research used analytic observational with crossectional approachment. Sample are 41 female handmade batik workers with total sampling as sample election technique. The data analyze used chi square test with 5% level error or ? = 0,05. Bivariate analyze at back position variable obtain p-value = 0,001 (< 0,05). Head and neck position variable obtain p-value = 0,108 (> 0,05). Hand range variable obtain p-value = 0,000 (< 0,05). Work sit position obtain p-value = 0,001 (< 0,05). Back position variable, hand range variable and work sit position have correlation with physical fatigue.